KETIDAKSETUJUAN KEGIATAN JUDI MERPATI DEMI MENJAGA KELESTARIANNYA (KHUSUSNYA PADA DAERAH KENJERAN, SURABAYA) - Kurnia Parmasari, Erlis; Agung Raynanda Putra N, Gede (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractThis research on pigeon gambling was made with the aim of informing residents that until now there are still many who carry out pigeon gambling activities, especially in the Kenjeran area of Surabaya. With the pigeon gambling activity, of course, indirectly harming their relatives, especially themselves if they do this, because if they fail, they will bet to pay the money according to the agreement. Where it is not profitable at all, but rather an addiction or desire more to hope to win and produce quickly. Pigeon gambling is a game using birds that are contested to compete with the flying speed of the pigeons until they reach the finish line that has been prepared and determined by the “adu doro” (pigeon fighting) committee. In Surabaya, especially in the Kenjeran area, the existence of